PENGARUH METODE PERMAINAN BAHASA TERHADAP KETERAMPILAN MENULIS KARANGAN NARASI DI SEKOLAH DASAR PONTIANAK - Nurmi, . (Jurnal Pendidikan dan Pembelajaran Khatulistiwa, 2017)
Abstract The purpose of this study was to describe the influence of Indonesian language learning to apply the language game method of narrative writing skill in class III SDN 29 Pontianak Kota. This research uses experimental experimental type experimental method with time series design experiment design. The population in this study were all students of class III SDN 29 Pontianak Kota consisting of three classes. The sample of this research is class IIIA which amounted to 24 students. Instrument in the form of test with description form as much as 1 problem. Data collection techniques use measurement techniques. Hypothesis test results using t-test (t test dependent) obtained t_ (count) of 28,3072 for dk = 23 and ? = 5% obtained t_ (table) of 2.069, which means t_hitung> t_tabel (28,3072> 2,069) , From the calculation of effect size (ES), obtained ES of 1.93. So, it can be concluded that there is influence of language game method to narrative writing skill in class III SDN 29 Pontianak Kota. Keywords: Influence, Game Method Language Type Post Picture, Narrative Writing Skills Writing Skills